Conceptual Model of Blockchain Technology for Chicken Meat Supply Chain in Yogyakarta City - Yeyet Maryasa; Utaminingsih Linarti (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The limited number of Chicken Slaughterhouses that already have a halal certificate in Yogyakarta city, causes a limited number of chicken meat supplies that have been certified halal. Even though the majority of people in the Yogyakarta city are muslim. Therefore, halal guarantees for products concumed by the puplic are very important. One way that can be done to help track guarantees of halal product is to use blockchain technology. Blockchain can be used to assist in tracking information related to chickhen meat, so that it can increase transparency and increase consumer confidence regarding chichken meat product. The purpose of this research is to design a blockchain model on the chickhen meat supply chain in Yogyakarta city, so that customers can get informastion about chickhen meat that is distributed along supply chain. Based on the result and analysis, it is known that blockchain can allow all stakeholders involved to be able to share the information they have into the blockchain system, which later this information will be tracked by all stakeholders. So that by sharing information into the system will create data transparency an minimze data usage, because information that can no longer be changed. Keywords: Blockchain, Supply Chain Management, Halal.